La proximidad sensible: estudios de caso de las relaciones a distancia desde la modernidad líquida de parejas heterosexuales, 2023. - Vásquez Aldaz, Allison Camila (2024)
Sensitive proximity clearly influences an emotional relationship, and it is about the closeness that you can have as a couple regardless of geographical location and the emotional connections that you can have despite physical separation. Long-distance relationships are geographically separated and cannot often see each other physically. These types of relationships arise due to various circumstances, such as migration, work, studies, but can be maintained thanks to technological advances and social networks. Liquid modernity greatly influences a long-distance relationship, since the causes it produces mean that a couple cannot be maintained for the long term and is ephemeral. In liquid modernity, lasting and real ties are not established; they are afraid of stability. The objective of this research is to analyze long-distance relationships and sensitive proximity from liquid modernity in cases of heterosexual couples. Qualitative methodology was used and for this case studies will be carried out to know precisely the reality of couples who maintain a long-distance relationship. Different types of research will be used, including basic, descriptive, field, exploratory and analytical, each of them contributes significantly to the study as they facilitate the direction of the research. The research work aims to know the reality of long-distance relationships from liquid modernity and sensitive proximity, they can significantly affect and are not lasting. In conclusion, the research allowed us to know the factors that affect long-distance relationships in the context of liquid modernity, such as the influence of technology, individualization, and constant adaptation since they play an important role in the configuration of relationships. from distance. Couples face challenges due to geographic separation, however, digital communication balances the dynamics and interactions between the couple. Keywords: sensitive proximity, long-distance relationships, liquid modernity, heterosexual couples, liquid love.